Improving Self-Leadership through the MBKM Entrepreneurship Program for Undergraduate - Tutik Susilowati; Yosep Tegar Prameswara (Jurnal Pendidikan dan Pengajaran, 2025)
Research on entrepreneurship has been conducted, but studies linking entrepreneurship in the Merdeka Curriculum of the Merdeka Campus (MBKM) with self-leadership are still limited. Preliminary studies show that the level of self-leadership among students is still low, although this skill is important for success in entrepreneurship as well as in everyday life. This study aims to analyse the impact of MBKM's entrepreneurship programme on increasing students' self-leadership. Using quantitative methods with Partial Least Squares Structural Equation Modeling (PLS-SEM), this study involved 152 students who participated in the MBKM independent entrepreneurship programme, with a sample of 115 students purposively selected. Data was collected using a questionnaire based on a 1-5 Likert scale. The results of the analysis show that the MBKM Entrepreneurship Programme has a significant effect on increasing students' self-leadership. Gender was not found to be a significant moderating variable, indicating that the programme is inclusive and provides equal benefits to men and women. This study suggests that the MBKM entrepreneurship programme can be an effective tool in developing students' self-leadership. The implication is that universities and study programmes are advised to integrate the MBKM Independent Entrepreneurship Programme into the curriculum to support the development of entrepreneurial potential, which is ultimately expected to enable graduates to create jobs and reduce the number of unemployed in Indonesia.